2022
DOI: 10.3389/fpsyt.2022.877934
|View full text |Cite
|
Sign up to set email alerts
|

War Experience, Daily Stressors and Mental Health Among the Inter-taliban Generation Young Adults in Northern Afghanistan: A Cross-Sectional School-Based Study

Abstract: ObjectivesThe specific objectives of the study are to examine the mental health (depression and anxiety) of the first generation of post-Taliban government and compare these measures with its preceding generation, and to assess war experience of the first generation of post-Taliban government. We also wanted to assess the daily stressors and their contribution to the mental health, and to assess mental health as a result of war experiences and daily stressors with respect to demographic measures such as sex, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 25 publications
1
4
0
3
Order By: Relevance
“…In this study, females expressed more concerns than men which is in congruence with other studies in Afghanistan ( 16 ). To date, women report a greater tendency to worry than men and various theories have attempted to explain the gender differences ( 9 ).…”
Section: Discussionsupporting
confidence: 92%
“…In this study, females expressed more concerns than men which is in congruence with other studies in Afghanistan ( 16 ). To date, women report a greater tendency to worry than men and various theories have attempted to explain the gender differences ( 9 ).…”
Section: Discussionsupporting
confidence: 92%
“…16,[38][39][40][41] Gender differences in depression and anxiety are clearly pronounced in Afghanistan. 38,42,43 These are attributed to the systematic and institutional discrimination experienced by Afghan women in many parts of the country 44 including the system of purdah, a practice of strict gender segregation excluding women from public spaces. 45 Gender difference in mental health issues may also be related to the cultural 'straitjacket' governing the public expression of emotions, discouraging women to reveal forms of despair and men to show fear, grief or doubt, as this would bring shame on the family.…”
Section: Adult Mental Healthmentioning
confidence: 99%
“…Due to con icts and wars for the last four decades, the mental health of Afghans has been negatively impacted. In a study conducted in Mazar-i-Sharif, located in northern Afghanistan, in 2022, it was found that girls exhibited elevated levels of anxiety and depression when contrasted with boys (Razjouyan et al, 2022). In a study conducted in 2022, investigating mental health and suicidality among university students in Afghanistan, ndings revealed that 69.7% exhibited clinical indicators of depression subsequent to the Taliban takeover in 2021 (Naghavi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%